Global tensions in financial markets - Kensinger, John W. (Research in finance,, 2018)
'Research in Finance' seeks to provide a collection of quality research articles that reflect the current and primary issues in financial markets. Contributions include finance theory and financial practice, plus accounting issues such as reporting derivatives positions, reflecting intangible holdings, or predicting financial distress. The volume starts with empirical investigations of the impact from macroeconomic variables upon equity values in emerging economies compared with developed economies. Next is an empirical affirmation of the efficiency of the Midcontinent Independent System Operator (MISO) electricity exchange. Next we find several investigations into the efficacy of efforts to stimulate the arousal of emerging nations around the world.